Galleria mellonella as a model system to study virulence potential of mucormycetes and evaluation of antifungal treatment. (19th June 2018) - Maurer, Elisabeth; Hörtnagl, Caroline; Lackner, Michaela; Grässle, Denise; Naschberger, Verena; Moser, Patrizia; Segal, Esther; Semis, Margarita; Lass-Flörl, Cornelia; Binder, Ulrike
Abstract: Mucorales can cause cutaneous to deep-seated infections, mainly in the immunocompromised host, resulting in high mortality rates due to late and inefficient treatment. In this study, Galleria mellonella larvae were evaluated as a heterologous invertebrate host to study pathogenicity of clinically relevant mucormycetes ( Rhizopus spp., Rhizomucor spp., Lichtheimia spp., Mucor spp.). All tested species were able to infect G. mellonella larvae. Virulence potential was species-specific and correlated to clinical relevance. Survival of infected larvae was dependent on (a) the species (growth speed and spore size), (b) the infection dose, (c) the incubation temperature, (d) oxidative stress tolerance, and (e) iron availability in the growth medium. Moreover, we exploited the G. mellonella system to determine antifungal efficacy of liposomal amphotericin B, posaconazole, isavuconazole, and nystatin-intralipid. Outcome of in vivo treatment was strongly dependent upon the drug applied and the species tested. Nystatin-intralipid exhibited best activity against Mucorales, followed by posaconazole, while limited efficacy was seen for liposomal amphotericin B and isavuconazole. Pharmacokinetic properties of the tested antifungals within this alternative host system partly explain the limited treatment efficacy. In conclusion, G. mellonella represents a useful invertebrate infection model for studying virulence of mucormycetes, while evaluation of treatment response was limited.